The Impact of Human Resources Strategies on Worker’s Performance in Construction Project - Teo, Ming En; Sarpin, Norliana; Seow, Ta Wee; Shafii, Haryati (Research in Management of Technology and Business, 2022)
Every construction organization has its own human resources department (HRM) to handle the issues related to workers in order to ensure the construction activities runs smoothly and completed on time. However, there have still occur delayed in construction projects in Malaysia either in public or private sectors where about 73.60 percent are due to issues related to worker’s productivity. Therefore, the objectives of the study are to identify the importance of human resources management strategies, to identify the main human resources management strategies used to improve worker’s performance and to study the impact of human resources management strategies towards worker performance in construction project. This study involves Grade 7 contractors in Johor Bahru and the respondents are included senior management level personnel in contractor organization namely project manager, senior manager or site manager. To achieve the study objectives, quantitative method was adopted where questionnaire survey was conducted to 85 respondents. The data collected was then analyse by using the Statistical Package for the Social Science (SPSS) software. This study shows that the main importance of HR strategies are including to monitors the culture, to retain and motivate employee to accomplish company's goal and to resolve conflicts. Meanwhile the main HR strategies used to improve construction worker’s performance is human resources following up strategy. In addition, the impact of human resources management strategies towards worker performance in construction project in many aspects such as level of competencies of workers, level of quality and quantity of tasks, level of knowledge of work requirements and the level of perseverance and dedication are also had been determined. In conclusion, HR strategies such as human resources follow-up strategy and training and development strategy can improve the worker’s performance from aspects of competencies of workers or level of knowledge of work requirement and consequently can improve the productivity of workers in construction project.